Proceedings of the International Academic Conference on the Future of Game Design and Technology 2010
DOI: 10.1145/1920778.1920802
|View full text |Cite
|
Sign up to set email alerts
|

Gameplay evaluation of the trackball controller

Abstract: We present a study of user performance in a First Person Shooter game comparing a prototype trackball controller, a standard game controller, and a keyboard and mouse. The prototype controller replaces the right analog stick of a standard game controller (used for pointing and camera control) with a trackball. To measure the performance of the three input devices, participants played two games. Penguin Hunt measured the number of target hits per minute, which was 28.1 with the keyboard and mouse, 22.9 with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…In our study, no significant differences were found between mouse and touchscreen in the three pointing and dragging tasks. We found that touchscreen was slightly faster than mouse for pointing tasks but slower for dragging‐and‐dropping tasks, in consistent with previous studies (Chen & Or, 2017; Forlines et al, 2007; MacKenzie et al, 1991, 2001; Natapov et al, 2009). One possible reason could be that touchscreen enables operators to point the screen directly, a way matching with the naturalness of selecting and clicking with the fingers (Forlines et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, no significant differences were found between mouse and touchscreen in the three pointing and dragging tasks. We found that touchscreen was slightly faster than mouse for pointing tasks but slower for dragging‐and‐dropping tasks, in consistent with previous studies (Chen & Or, 2017; Forlines et al, 2007; MacKenzie et al, 1991, 2001; Natapov et al, 2009). One possible reason could be that touchscreen enables operators to point the screen directly, a way matching with the naturalness of selecting and clicking with the fingers (Forlines et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Input devices are essential computer accessories for fundamental operations (e.g., pointing and dragging) in human–computer interaction (HCI), especially with graphical user interfaces (GUIs) (Cassidy et al, 2019; Cockburn et al, 2012). While previous studies have compared several traditionally used input devices (e.g., mouse, touchscreen, and trackball) in pointing tasks (Chen & Or, 2017; Hertzum & Hornbæk, 2010; Natapov et al, 2009) and dragging tasks (Cassidy et al, 2019; Chen & Or, 2017; Cockburn et al, 2012; Wood et al, 2005), it remains unclear about the performance of some newly developed input devices operated by gestures (e.g., remote hand‐controller) (Jones et al, 2019). As compared with traditional ones, it could be fundamentally different to use these new input devices as no physical contract is required when using gestures to interact with GUIs.…”
Section: Introductionmentioning
confidence: 99%
“…Utility ratings. A subjective evaluation of the controller in accordance with ISO-9241 on device comfort was assessed via a questionnaire of 8 items answered on a 5-points Likert scale, adapted from [22]. For the items smoothness during operation, general comfort and overall useability, higher scores indicate better fitness.…”
Section: Task Designmentioning
confidence: 99%
“…Commercial video games use aiming assistance mainly on console systems; PC-based games generally do not employ aiming assistance because mice are more precise than the game controllers used in consoles [20]. Despite their use in games, aiming assistance for multiplayer game balancing is not a central component of commercial games.…”
Section: Aim Assistance Techniquesmentioning
confidence: 99%